G397(P) Use of a short instructional video improves performance of neonatal resuscitation skills. (27th April 2016) - Knight, KM; Boutros, S; Harper, C; Aladangady, N; Fleming, P
Abstract : Introduction: In the United Kingdom, practical training in neonatal resuscitation is a requirement for neonatal practitioners. Good quality, effective resuscitation can improve short and long term outcomes and prevent many immediate perinatal complications. Resuscitation skills deteriorate rapidly if not used daily. A particularly rapid loss of skills occurs in the first 3–6 months after attending a resuscitation course. Currently there is no formal program for refresher training in neonatal resuscitation skills in the four year period until mandatory recertification. E-learning and video based training has been shown to be an effective means of teaching and refreshing adult and paediatric resuscitation skills. Aims/Method: This study evaluated whether a 'refresher' training video could improve performance in neonatal healthcare professionals. We produced a 3 min video with voiceover, demonstrating key neonatal resuscitation skills. Eighty six clinical staff members (32 midwives, 31 neonatal nurses and 23 doctors) volunteered to participate in the study; their neonatal resuscitation skills were assessed before and after viewing the video. Results: There was a statistically significant improvement in all skills assessed across all professional groups after viewing the video. Key results: 59% of midwives delivered effective inflation breaths pre video compared to 96% post video (P = 0.0005). Nurses' checking of the correct set up of resuscitation equipment improved from 64% to 93% (P = 0.0001). Sixty-five percent of doctors checked the Positive End-Expiratory (PEEP) pressures before seeing the video, increasing to 100% afterwards (P = 0.0072). Conclusion: Videos such as this could form part of a training package available to staff who wish to refresh their resuscitation skills through self-directed learning, or become part of mandatory training updates.